Options for day-ahead market and power exchange in the Republic of Macedonia - Mateska, A. Krkoleva; Krstevski, P.; Borozan, V.; Angelov, J.; Taleski, R.; Skanlund, A. B.; Rennesund, M. H.; Wolst, J.; Magnus, E. (IEEE, 2015)
The objective of the paper is to investigate a possible solution for a "marketplace" for day-ahead trade and the role of a Power Exchange (PX) in the Republic of Macedonia. In general, the solution refers to how the market is organized, how roles, responsibilities and functions are distributed between market service providers (e.g. power exchanges, brokers, clearing houses), transmission system operators, regulators and market players. In this paper, the solution determines the role and responsibilities of the future organized marketplace for electricity trade and addresses the regulatory requirements. The broader aim of the research presented within this paper is to identify the means of integrating the future Macedonian PX into the region of South Eastern Europe and the integrated Pan-European electricity market.
Keywords: day-ahead market, power exchange